Payment and Motivation: Female Community Health Volunteers in Nepal - Bashyal, Lalita Kaundinya (Dhaulagiri Journal of Sociology and Anthropology, 2023)
The paper attempts to critically discuss the payment issue among Female Community Health Volunteers (FCHV) in Nepal. It examines how the Female Community Health Volunteers experience such issues and the impact on them. The payment issues among Community Health Workers are very contentious, particularly in developing countries. The prevalence of this issue in Nepal merits critical attention. The paper further examines Female Community Health Volunteers’ motivation to work despite the numerous challenges. The paper is based on fieldwork in the Bardiya District of Nepal where most respondents expect to receive some basic remuneration for their service regularly. The question, therefore, arises for examination as to why they are unwilling to leave their position even though they do not receive any financial rewards for community service. Social status, mobility, gaining new knowledge, participating in various programs, and building relationships with others are some of the motivating factors for FCHVs.